Synthesis of Nodupetide Analogue: Substitution of β- to α-hydroxy Acid - Farah, Harra Ismi; Supratman, Unang; Hidayat, Ace Tatang; Maharani, Rani (Trends in Sciences, 2024)
Nodupetide, a cyclodepsipeptide with the potential as an antimicrobial agent, was isolated from the fermentation of the fungi Nodulisporium sp strain IFB-A163. It possessed antibacterial activity against Pseudomonas aeruginosa and revealed an insecticidal activity. In our effort to synthesized nodupeptide, the preparation of the (3S,4S)-3-hydroxy-4-methylhexanoic acid (HMHA) as one of the nodupetide residue was found to be challenging, where it is not commercially available and the synthetic trial of the HMHA was not successful. This led us to synthesize nodupetide derivative by replacing HMHA with its a-hydroxy acid to give the analogue [(2S,3S)-Hmp]2-nodupetide. A combination of solid- and solution-phase peptide synthesis was applied in the synthesis nodupetide analogue. Esterification on the resin for synthesis [(2S,3S)-Hmp]2-nodupetide was achieved by placing the reaction at the last stage of the linear peptide synthesis and obtained in overall yield of 4.3 %. We also conducted antimicrobial activity screening for [(2S,3S)-Hmp]2-nodupetide and its linear precursor, showing inactive activity. The alter of hydrophobicity on the nodupetide analogue has very important role in the difference of bioactivity compared to their parent compound. HIGHLIGHTS The synthesized analogue compound has not been reported previously we studied the synthesis strategy of cyclodepsipeptide. We studied the change of beta hydroxy carboxylic acid residue to alpha hydroxy carboxylic acid, which has a very significant effect on biological activity. GRAPHICAL ABSTRACT